2018
DOI: 10.31384/jisrmsse/(2018).16.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Profitability in Life and Non-Life Insurance Sector of Pakistan: An Endogenous and Exogenous Evaluation

Abstract: The study is designed to identify the determinants of profitability in the insurance industry of Pakistan. The panel data set of 41 insurance companies (life, non-life, and takaful insurance) from 2007-2017 was employed. Hausman's specification and Breusch-Pagan Lagrange multiplier (LM) tests have selected the most appropriate test i.e. fixed effect and pooled OLS model for this study. The results of pooled OLS and fixed effect model reveal that insurance specific and macroeconomic factor like leverage, busine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 2 publications
1
1
0
Order By: Relevance
“…Holding other independent variables constant at their average value, when liquidity increased by 1%, return on asset (ROA) of sampled Ethiopian insurance companies would increase by 5.74% and the relationship is statistically significant at 5% of significance level. This positive relationship is not expected but the result is consistent with previous studies which found a positive relationship between liquidity and ROA, for instance, Abate (2012) and Teklit and Jasmindeep (2017) liquidity has negative and significant effect on profitability but on the other hand, Behailu and Wolde (2016), Rahman et al (2018) and Sumaira and Amjad (2013) conclude liquidity has positive and significant effect on profitability. According to Naveed et al (2010), Charumathi (2012) and Emine (2015).…”
Section: Inferential Statisticssupporting
confidence: 88%
“…Holding other independent variables constant at their average value, when liquidity increased by 1%, return on asset (ROA) of sampled Ethiopian insurance companies would increase by 5.74% and the relationship is statistically significant at 5% of significance level. This positive relationship is not expected but the result is consistent with previous studies which found a positive relationship between liquidity and ROA, for instance, Abate (2012) and Teklit and Jasmindeep (2017) liquidity has negative and significant effect on profitability but on the other hand, Behailu and Wolde (2016), Rahman et al (2018) and Sumaira and Amjad (2013) conclude liquidity has positive and significant effect on profitability. According to Naveed et al (2010), Charumathi (2012) and Emine (2015).…”
Section: Inferential Statisticssupporting
confidence: 88%
“…In a study on Malaysia, GDP per capita was found to be significantly positive in determining the demand for life insurance products while the impact of Inflation was found negative (Noor et al, 2020). Rahman et al (2018) found leverage, business risk, and the rate of inflation to have a significantly negative impact on the performance of insurance companies in Pakistan. Inflation, interest rate, life expectancy, dependency ratio, and urbanisation were found to be positive in case of demand for life insurance in Ethiopia, and GDP per capita was found to be negative (Meko et al, 2019).…”
Section: Literature Surveymentioning
confidence: 99%